The Role of Pyruvate in Protecting 661W Photoreceptor-Like Cells Against Light-Induced Cell Death. (1st November 2016) - Natoli, Riccardo; Rutar, Matt; Lu, Yen-Zhen; Chu-Tan, Joshua A.; Chen, Yuwei; Saxena, Kartik; Madigan, Michele; Valter, Krisztina; Provis, Jan M.
ABSTRACT: Purpose : Light is a requirement for the function of photoreceptors in visual processing. However, prolonged light exposure can be toxic to photoreceptors, leading to increased reactive oxygen species (ROS), lipid peroxidation, and photoreceptor cell death. We used the 661W mouse cone photoreceptor-like cell line to study the effects of pyruvate in protecting these cells from light-induced toxicity. Methods : 661W cells were exposed to 15, 000 lux continuous bright light for 5 hours and incubated in Dulbecco's modified eagle medium (DMEM) with various concentrations of pyruvate. Following light damage, cells were assessed for changes in morphology, cell toxicity, viability, and ROS production. Mitochondrial respiration and anaerobic glycolysis were also assessed using a Seahorse Xfe96 extracellular flux analyzer. Results : We found that cell death caused by light damage in 661W cells was dramatically reduced in the presence of pyruvate. Cells with pyruvate-supplemented media also showed attenuation of oxidative stress and maintained normal levels of ATP. We also found that alterations in the concentrations of pyruvate had no effect on mitochondrial respiration or glycolysis in light-damaged cells. Conclusions : Taken together, the results show that pyruvate is protective against light damage but does not alter the metabolic output of the cells, indicating an alternative role for pyruvate in reducing oxidative stress. Thus, sodium pyruvate is a possible candidate for the treatment against the oxidative stress component of retinal degenerations.